2016
DOI: 10.1002/adfm.201603336
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of a π–π Stacked Dual Anticancer Drug Combination with Nanocarriers for Overcoming Multidrug Resistance and Tumor Metastasis

Abstract: The multidrug resistance (MDR) of cancer cells is a major obstacle in cancer chemotherapy and very few strategies are available to overcome it. Here, a new strategy is developed to codeliver a π–π stacked dual anticancer drug combination with an actively targeted, pH‐ and reduction‐sensitive polymer micellar platform for combating multidrug resistance and tumor metastasis. In contrast to other methods, two traditional chemotherapeutics, doxorubicin (DOX) and 10‐hydroxycamptothecin with complex aromatic π–π con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 55 publications
0
79
0
Order By: Relevance
“…The anticancer drug DOX, interacting with DNA by intercalation and inhibition of macromolecular biosynthesis, can be encapsulated into nanoparticles . In our case, DOX was loaded in the hydrophobic cores.…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer drug DOX, interacting with DNA by intercalation and inhibition of macromolecular biosynthesis, can be encapsulated into nanoparticles . In our case, DOX was loaded in the hydrophobic cores.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] NPs are generally thought to enter tumor site via enhanced permeability and retention (EPR) effect, but the extremely complex tumor microenvironment (TME), which includes dense extracellular matrices (ECMs), high cell packing density, increased interstitial flow pressure (IFP), and slow interstitial flow velocity, constitutes a variety of barriers to NPs delivery and results in poor penetration and inadequate retention in deep tumor tissues, dramatically weakening the accumulation capability of NPs at tumor sites. [ 2 ] It was reported that the median of NPs accumulated in tumor in vivo was only ≈0.7% of the injected dose (ID), whose corresponding % ID per gram of tissue was ≈4.2%. [ 3 ] The inability of NPs to intratumoral accumulate efficiently means poor therapeutic efficacy, systemic toxicity, and possible drug resistance.…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 ] The inability of NPs to intratumoral accumulate efficiently means poor therapeutic efficacy, systemic toxicity, and possible drug resistance. [ 2f ] To achieve the maximum chemotherapeutic efficacy, the accumulation of abundant NPs in tumor is of great importance. However, it is currently full of challenges to increase intratumoral accumulation of NPs.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, intracellular organelle microenvironments such as low pH in endo-/lysosomal compartments are also available for triggering drug release from drug-carrier conjugates which contain acid-cleavable linkages. 25,26 In the aim to overcome the P-gp-mediated MDR, in this study we report novel surface charge-reversible polymer micelles which could cascade release PTX and DSF inside drug-resistant tumor cells (Scheme 1). The carriers were constituted with succinic anhydride-modified PTX (SA-PTX) and 2,3-dimethylmaleic anhydride (DMA)-conjugated poly(ethylene glycol)-b-poly(l-lysine).…”
mentioning
confidence: 99%